Examining the impact of anisotropic particle orientation in a polymer matrix on the electrical properties of composite materials - Anna Stepashkina; Khurram Shehzad (Zaštita Materijala)
A number of works have experimentally shown the significant influence of mechanical stretching on the electrically conductive properties of composite polymer materials. Thus, stretching polymer composite films and filaments can lead to deterioration in electrical conductivity properties which can significantly affect the characteristics of products made from such materials. The research conducted in this study focuses on simulation the impact of anisotropic particle orientation within a polymer matrix and mechanical stretching on the electrical properties of composite materials. Based on the Boltzmann statistics, an expression was obtained that allows predicting the change in electrical conductivity during the stretching of polymer composite samples. The Monte Carlo method was used to simulate the destruction of a percolation chain of conductive particles during stretching.